Mediating role of systemic immune-inflammation index between heavy metal exposure and hepatic steatosis/hepatic fibrosis: evidence from NHANES 2005–2020 - Ningning Wang; Ningning Wang; Ningning Wang; Xuying Li; Xuying Li; Xuying Li; Rui He; Rui He; Xiujuan Zheng; Xiujuan Zheng; Xiujuan Zheng; Mingqi Li; et al. (Frontiers in Nutrition)
BackgroundModerate heavy metals can lead to the occurrence of liver injury, but the specific mechanism remains unclear.MethodsThis study, based on data from the National Health and Nutrition Examination Survey (NHANES), analyzed associations between 10 heavy metals and hepatic injury in 5,613 adults, with a focus on the mediating role of the Systemic Immune-Inflammation Index (SII). Partial correlation analysis, weighted linear regression, weighted quantile sum (WQS) regression, and mediation effect models were used in the study.ResultsSII showed significant negative correlations with hepatic fibrosis markers (FIB-4: r = −0.290; NFS: r = −0.382, both P < 0.001) but no association with hepatic steatosis indices. Arsenic (As), cobalt (Co), and cesium (Cs) were identified as critical metals linking fibrosis indicators and SII. As mediated its pro-fibrotic effects by completely suppressing SII (OR = 0.0220–0.0581), while Co promoted NFS risk through complete mediation by SII (Q2 vs. Q1 OR = 1.26). Conversely, Cs exhibited anti-fibrotic protectionvia complete positive mediation through SII.ConclusionThe findings demonstrate that Heavy metals differentially regulate immune-inflammatory pathways to influence hepatic fibrosis progression, providing new evidence for the mechanisms of environmental exposure-induced hepatic injury.